Effect of Coal Dust Exposure on the SOD Activity and the Oxidative DNA Damage in Asthmatic Mice - Windy Yuliana Budianto; Husnul Khotimah; Eko Suhartono (The Indonesian Biomedical Journal, 2019)
BACKGROUND: Coal dust is known to trigger hypersensitivity and inflammation of the respiratory tract as it increases oxidative stress leading to asthma. To date, the relationship of coal dust exposure in the pathomechanism of asthma remains unclear. This study was aimed to examine the effect of coal dust exposure on the superoxide dismutase (SOD) activity and the oxidative DNA damage indicated by increased serum 8-hydroxy-2' -deoxyguanosine (8-OHdG) in asthmatic mice.METHODS: Twenty-four female balb/c mice were divided into four groups. The first group was the control group. The second group was the negative control group which composed of mice exposed to coal dust particles. The third group was composed of ovalbumin (OVA)-sensitized mice. The fourth group was composed of OVA-sensitized mice and exposed to coal dust particles. The inflammatory process was identified by serum interleukin (IL)-13 concentration using Enzyme-linked Immunosorbent Assay (ELISA) method. Meanwhile, the oxidative stress was examined by measuring the SOD activity using the Nitro Blue Tetrazolium (NBT) method, and the 8-OHdG concentration was quantified by ELISA method.RESULTS: There was an increasing IL-13 in OVAtreated coal dust exposed group along with the increment of 8-OHdG (statistically not significant). SOD activity measured in serum was decreased in all groups (p>0.05). Combination of OVA and coal dust showed the worst effect on IL-13, 8-OHdG and SOD activity.CONCLUSION: Coal dust exposure for four weeks does not adequately induce the oxidative DNA damage in asthmatic mice.KEYWORDS: asthma, coal dust, IL-13, SOD, 8-OHdG